Impacto de las acciones de la responsabilidad social de la empresa agroindustrial camposol s.a. en las condiciones de bienestar en el centro poblado san jose - viru - 2013 - Gabriel Narvaez, Fiorella Noemi (2014)
This thesis report was made in order to know the "Action Impact of Corporate Social Responsibility Camposol SA Agroindustrial Welfare Conditions in the slum area of New Chao Setiembre - 2013." Research is descriptive in nature and used deductive methods - inductive statistical techniques using observation, interview and survey. The study was carried out in the Settlement Humano Nuevo Chao taking as sample universe of 100 families. The people believe that the intervention of the company within the Settlement Camposol SA has been instrumental in improving their quality of life, allowing many people to access job positions also state that the company is developing several actions benefiting the population in turn could make greater shares in favor of the population. In the area of education has been improved: school infrastructure has been contributed by donating school supplies, etc. another factor intervention agribusiness company Camposol SA, is the health sector, providing medical equipment, medical campaigns, etc. Likewise also enhanced employability in the Settlement Humano decreasing unemployment not only in the human settlement, but throughout the district. Shares of the company clung community can raise the quality of life of the population.